Bivalirudin versus heparin monotherapy in non-ST-segment elevation myocardial infarction. Issue 6 (1st September 2019) - Erlinge, David; Koul, Sasha; Omerovic, Elmir; Fröbert, Ole; Linder, Rikard; Danielewicz, Mikael; Hamid, Mehmet; Venetsanos, Dimitrios; Henareh, Loghman; Pettersson, Björn; Wagner, Henrik; Grimfjärd, Per; et al.
Abstract: Background: The optimal anti-coagulation strategy for patients with non-ST-elevation myocardial infarction treated with percutaneous coronary intervention is unclear in contemporary clinical practice of radial access and potent P2Y12-inhibitors. The aim of this study was to investigate whether bivalirudin was superior to heparin monotherapy in patients with non-ST-elevation myocardial infarction without routine glycoprotein IIb/IIIa inhibitor use. Methods: In a large pre-specified subgroup of the multicentre, prospective, randomised, registry-based, open-label clinical VALIDATE-SWEDEHEART trial we randomised patients with non-ST-elevation myocardial infarction undergoing percutaneous coronary intervention, treated with ticagrelor or prasugrel, to bivalirudin or heparin monotherapy with no planned use of glycoprotein IIb/IIIa inhibitors during percutaneous coronary intervention. The primary endpoint was the rate of a composite of all-cause death, myocardial infarction or major bleeding within 180 days. Results: A total of 3001 patients with non-ST-elevation myocardial infarction, were enrolled. The primary endpoint occurred in 12.1% (182 of 1503) and 12.5% (187 of 1498) of patients in the bivalirudin and heparin groups, respectively (hazard ratio of bivalirudin compared to heparin treatment 0.96, 95% confidence interval 0.78–1.18, p =0.69). The results were consistent in all major subgroups. All-cause death occurred in 2.0% versus 1.7% (hazard ratio 1.15, 0.68–1.94, p =0.61), myocardial infarction in 2.3% versus 2.5% (hazard ratio 0.91, 0.58–1.45, p =0.70), major bleeding in 8.9% versus 9.1% (hazard ratio 0.97, 0.77–1.24, p =0.82) and definite stent thrombosis in 0.3% versus 0.2% (hazard ratio 1.33, 0.30–5.93, p =0.82). Conclusion: Bivalirudin as compared to heparin during percutaneous coronary intervention for non-ST-elevation myocardial infarction did not reduce the composite of all-cause death, myocardial infarction or major bleeding in non-ST-elevation myocardial infarction patients receiving current recommended treatments with modern P2Y12-inhibitors and predominantly radial access.